2016
DOI: 10.1101/gad.279190.116
|View full text |Cite
|
Sign up to set email alerts
|

Modeling invasive lobular breast carcinoma by CRISPR/Cas9-mediated somatic genome editing of the mammary gland

Abstract: Large-scale sequencing studies are rapidly identifying putative oncogenic mutations in human tumors. However, discrimination between passenger and driver events in tumorigenesis remains challenging and requires in vivo validation studies in reliable animal models of human cancer. In this study, we describe a novel strategy for in vivo validation of candidate tumor suppressors implicated in invasive lobular breast carcinoma (ILC), which is hallmarked by loss of the cell-cell adhesion molecule E-cadherin. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 41 publications
1
110
0
Order By: Relevance
“…We have shown that intraductally injected lentiviruses can target tumor-initiating cells of both the basal and the luminal compartment, allowing modeling of both ILC and basallike tumors in mice with the corresponding set of relevant predisposing alleles. For example, intraductal injection of Cre-encoding lentiviruses in Cdh1 F/F ;Pten F/F mice induced the formation of ILCs that were undistinguishable from the ILCs arising in the original WAPcre;Cdh1 F/F ; Pten F/F model (Annunziato et al 2016). Somatic Cre delivery may more accurately recapitulate sporadic tumor initiation by allowing titratable and spatiotemporally controlled delivery of viruses to mammary tissue.…”
Section: Nongermline Gemms Of Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that intraductally injected lentiviruses can target tumor-initiating cells of both the basal and the luminal compartment, allowing modeling of both ILC and basallike tumors in mice with the corresponding set of relevant predisposing alleles. For example, intraductal injection of Cre-encoding lentiviruses in Cdh1 F/F ;Pten F/F mice induced the formation of ILCs that were undistinguishable from the ILCs arising in the original WAPcre;Cdh1 F/F ; Pten F/F model (Annunziato et al 2016). Somatic Cre delivery may more accurately recapitulate sporadic tumor initiation by allowing titratable and spatiotemporally controlled delivery of viruses to mammary tissue.…”
Section: Nongermline Gemms Of Breast Cancermentioning
confidence: 99%
“…3). Regarding CRISPR-based in vivo editing approaches, we and others have shown that somatic delivery of the bacterial Cas9 protein has the considerable drawback of eliciting strong and specific immune responses in immunocompetent animals (Wang et al 2015;Annunziato et al 2016). This problem can be overcome by employing knock-in models that are tolerant to Cas9 because of constitutive or conditional expression of Cas9 or catalytically inactive dCas9-effector fusions (which allow for transcriptional silencing/activation of endogenous alleles) (Platt et al 2014;Sánchez-Rivera and Jacks 2015).…”
Section: Nongermline Gemms Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A new study published by Jonkers and colleagues in Genes & Development [1] provides a timely example of how CRISPR has spawned a new in vivo toolkit equipped to deal with the need for increasingly complex genetic mouse models. Using a viral-based approach, Annunziato et al show that Cas9-mediated genome editing can produce genetically and histologically accurate invasive breast cancers in mice and thus delineate a path forward to putatively define genetic drivers of this disease and develop tailored preclinical model systems.…”
mentioning
confidence: 99%
“…As expected, tumor nodules showed efficient editing of the target Ctnnb1 locus, to create activating S45F mutations (Figure 3h). An alternate approach to in vivo somatic base editing is the generation of temporally regulated transgenic strains, which enables the manipulation of tissues and cell types that cannot be easily transfected in vivo, and avoids the potential immunogenicity of exogenous Cas9 delivery 21,22 . We generated knock-in transgenic mouse embryonic stem cells (ESCs), in which BE3 or RA expression is controlled by the TRE promoter.…”
mentioning
confidence: 99%